World Trends in Digitization of Enterprises’ Economic Processes (Laisvalaikio tyrimai, 2021)
Research object. Research problem. Recently, both in the economic theory and in the practical activities in several countries, the concept of digital economy has emerged. Digitalization of processes, digital transformation, digital education, digital marketing – the word “digital” has been on everyone’s lips for several years now. The current crisis with its bomb-blasting effect has already proved that not only is the future of business a shift to digital technology, but the present is at stake if we do not act quickly. The beginning of the 21st century brought the development of digital technologies through the information revolution and the processes of economic globalization. Information in society and management processes has become a major resource. In the hands of man, it is transformed into knowledge, and social as well as economic relations are increasingly transferred to the network space. The development of digital culture is a key factor in the digital transformation of market actors. The authors show that at the present stage the institutional structure of a transformational society has features and requires the formation of a digital economy, which is now an actual task.The problem is the study. Although the crisis has to some extent mitigated the widening technological divide, the development of the digital economy in individual countries needs further government regulation and institutionalization.  In the near future, employers will face labour shortage to meet the new requirements, but the same acute problem will affect a large part of the working-age population, which will not be in demand in the new realities of digital life. Is the domestic economy ready for short- and medium-term digitalization, as the digital world has already entered our daily lives in most of its segments?The aim of the study is to reveal the peculiarities of the global trends of digital economic processes.Research methods. Analysis of scientific literature, synthesis, generalization. Scientific literature and theoretical interpretation to summarize the studies carried out on this topic, to find answers to what are the existing features of the current situation of digital economic development, because this phenomenon is interpreted on the basis of scientific analysis. The concepts will be analyzed, the most important concepts will be clarified and substantiated.Outcomes and conclusions. With the growing number of participants in digital transformation, both in individual countries and around the world, the issue of cybersecurity at the enterprise level, both at the state and international level, becomes more urgent. Therefore, there is a need to pay great attention to software and legislation (national and international) in the protection of the information space, as cybersecurity is the guarantor of “healthy” competition in the technological world. Analysis of global trends in the digitalization of the economic processes of enterprises confirms that such transformations will contribute not only to increasing the competitiveness of enterprises in world markets, but also to improving the quality and standard of the population.Keywords: digitalization, economics, digitalization trends.